Primary nasal tuberculosis - Manoj Kumar Pandey; Poornima Mishra; Anil Gupta (Indian Journal of Respiratory Care, 2020)
Tuberculosis can involve any part of body. Tubercular bacteria rarely involve nose as a primary site for infection. This site of involvement of Mycobacterium tuberculosis (MTB) is rarer even in endemic country like India. Here we are presenting a case of primary nasal TB.